ChemInform Abstract: Selective and Efficient Deoxygenation of Amine‐N‐Oxides with CeCl3·7H2O/Zinc System. Issue 40 (12th September 2013) - Yoo, Byung Woo; Jung, Ha Il; Kim, Se Heon; Ahn, Young Sun; Choi, Ji Yong
Abstract A variety of functional groups are compatible with the reaction conditions.